Structural and magnetic properties of the R10Fe90-xSix alloys with R=Y, Ce, Pr, Nd, Sm, Gd, Tb, Dy, Ho, and Er. (August 2018) - Yang, Wenyun; Zha, Liang; Lai, Youfang; Qiao, Guanyi; Du, Honglin; Liu, Shunquan; Wang, Changsheng; Han, Jingzhi; Yang, Yingchang; Hou, Yanglong; Yang, Jinbo; Yu, Xi; et al.
Abstract: In this study alloys with stoichiometry of R2 Fe17 and R10 Fe90-x Six (x = 0, 10, 15, 20) (R = Y, Ce, Pr, Nd, Sm, Gd, Tb, Dy, Ho, and Er) have been prepared. Structural transition from the ordered rhombohedral (OR) Th2 Zn17 -type structure and the ordered hexagonal (OH) Th2 Ni17 -type structure to their disordered structures (DR and DH) has been observed according to the XRD patterns. The lattice parameters were obtained by Rietveld analysis and based on the changing characteristic of the parameters, these samples are divided into two categories: alloys with R = Ce, Pr, Nd, Sm and alloys with R = Y, Gd, Td, Dy, Ho, Er. The lattice parameters of the two categories show different changing behavior. For example, from R2 Fe17 to R10 Fe90, the lattice parameters a decrease and c increase for the latter category, whereas for the former the lattice parameters a and c nearly have no change. In addition, increase of the ratio c/a has been found with increasing Fe or Si content, indicating the introduction of extra Fe dumbbells into the crystal cells, forming the DR or DH intermetallic compounds of R2-y (Fe, Si)17+2y . The obtained samples with disordered structure have shown better stability than the TbCu7 -type metastable materials and the higher Fe concentration gives promise of higher magnetization. The mixed-rare-earth effect has also been studied in the (Ce, R)10 Fe75 Si15 alloys and transition between the DR and DH structures has been realized by changing the mixed R-type or adjusting the Ce/R ratio. As for the magnetic properties, the Curie temperatures are increased remarkably by the introduction of Si and the saturation magnetizations of R10 Fe90-x Six are often higher than that of the R2 Fe17 alloys. Highlights: Disordered rhombohedral (DR) and hexagonal (DH) structures have been observed. Intermetallic compounds of R2-y (Fe, Si)17+2y have been successfully prepared. The obtained disordered samples showed better stability than the TbCu7 -type metastable materials. It has been proved that the Si can help to introduce Fe dumbbells into the crystal cells. The transition between the DR and DH structures has been realized. The Tc s have been increased remarkably by the introduction of Si. The Ms of R10 Fe90-x Six are often higher than that of the R2 Fe17 alloys.